Pola Fungsi Kalimat Tunggal dalam Kumpulan Cerpen “Cemara” Karya Hamsad Rangkuti sebagai Sumber Bacaan Siswa Kelas XI SMA - Ariska Novirinda Stefany; Aulia Lathifatul Chalda; Dwi Aulia Putri; Lilis Septiani; Siti Rizkia Latifa; Wahyu Wulan Setiyanti; Asep Purwo Yudi Utomo (STIKes Ibnu Sina Ajibarang, 2024)
The branch of grammar that studies sentence structure is syntax. Sentences consisting of subject (S), predicate (P), object (O), complement (Pel), and adverb (K) are structural types of syntax. The pattern of sentence function in each collection of short stories is different. The language in a short story usually contains various sentences such as description sentences, dialog sentences, and narrative sentences. A good sentence is a sentence that can express a complete thought or can reveal complete information. The purpose of this research is not only to analyze the sentence function pattern but also to discuss the ineffectiveness of the sentence in relation to the reading resources of grade XI SMA. There are two types of approaches in this research, namely descriptive qualitative methodological approach and syntactic theoretical approach. The method used in this research is the simak catat and padan method. The presentation methods used are formal and informal. The results of this study found 9 patterns of sentence functions, namely, SPPel, SPO, SP, SPK, SPOK, SPOPel, SPOPelK, SPPelK, and SPPelO. Although syntactic functions are not always filled in every sentence, at least the Subject and Predicate must be present because they are interrelated. In this study, ineffectiveness has also been found due to double subjects, use of conjunctions, ambiguity, use of synonyms, and waste of words. This makes the reader have difficulty in understanding the sentence. The benefit of this research is that it can find out the use of sentence function patterns in short stories including the relationship between elements such as subjects, predicates, objects, and clauses. So that it can produce a good and correct sentence structure. In addition, this research also presents the results of an overview of the variations in sentence structure and the importance of using good and correct grammar in its use to understand a text.